Peran Ganda Media Sosial dalam Penegakan Hukum Indonesia: Analisis Sosio-Legal antara Peluang Transparansi dan Risiko Erosi Due Process - Irwan Triadi; Febrian Rizky Akbar (Journal of Innovative and Creativity, 2025)
This socio-legal study analyzes the dual role of social media in Indonesia's criminal justice system from 2019 to 2024 through thematic analysis of 15 viral legal cases. The research demonstrates that while social media enhances transparency and accelerates investigations in 80% of cases examined, it simultaneously erodes fundamental due process principles in 53% of cases through trial by social media and digital vigilantism. The phenomenon of "no viral no justice" reveals a critical institutional failure, where law enforcement agencies have externalized case prioritization functions to digital virality metrics rather than maintaining equal application of law. The study introduces the concept of "justice outsourcing" to explain how public pressure forces hasty responses that may compromise the presumption of innocence and equality before the law. Through analysis of secondary data including regulatory frameworks, institutional reports, and verified digital documentation, this research identifies a central tension between substantive justice demands and procedural integrity. The findings reveal that law enforcement responses, while demonstrating adaptability, often sacrifice careful investigation protocols for rapid public satisfaction. The study proposes a collaborative governance model involving law enforcement, digital forensic specialists, and independent fact-checking communities, alongside regulatory updates to the Criminal Procedure Code (KUHAP) and the Information and Electronic Transactions Law (UU ITE), to mitigate disinformation risks while protecting suspect rights and maintaining due process standards in the digital public sphere.